2019
DOI: 10.1111/bjh.15971
|View full text |Cite
|
Sign up to set email alerts
|

Raman imaging highlights biochemical heterogeneity of human eosinophils versus human eosinophilic leukaemia cell line

Abstract: Summary Eosinophils are acidophilic granulocytes that develop in the bone marrow. Although their population contributes only to approximately 1–6% of all leucocytes present in the human blood, they possess a wide range of specific functions. They play a key role in inflammation‐regulating processes, when their numbers can increased to above 5 × 109/l of peripheral blood. Their characteristic feature is the presence of granules containing eosinophil peroxidase (EPO), the release of which can trigger a cascade o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…As discussed in the introduction, eosinophils and neutrophils are mostly differentiated based on the nucleus shape, granule content as well as the presence of lipid bodies (LBs) observed in optical and fluorescence microscopy as we found in Raman images depicted in Figure 3 [6,13,52]. In turn the fluorescence images of EOS and Ne stained with the Hoechst dye and combined with the Columbus analysis showed that these organelles mainly differed in their symmetry whereas the radius and compactness were almost identical.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…As discussed in the introduction, eosinophils and neutrophils are mostly differentiated based on the nucleus shape, granule content as well as the presence of lipid bodies (LBs) observed in optical and fluorescence microscopy as we found in Raman images depicted in Figure 3 [6,13,52]. In turn the fluorescence images of EOS and Ne stained with the Hoechst dye and combined with the Columbus analysis showed that these organelles mainly differed in their symmetry whereas the radius and compactness were almost identical.…”
Section: Discussionmentioning
confidence: 55%
“…We have previously reported the sensing capability of normal Raman scattering imaging for the detection of LBs in primary eosinophils and eosinophilic cell line EoL-1 [6]. Nevertheless, LBs are not formed in each cell under normal conditions and without additional stimulation, and thus the collection of Raman images of single cells to detect LBs is time consuming.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations